Serum interleukin-18 levels are associated with physical activity in Japanese men. - Kanae Oda (Public Library of Science (PLoS), 2013)
Objective To investigate the link between serum interleukin-18 (IL-18) levels and physical activity in Japanese men. Methods A total of 81 men (45.7±17.6 years old) was enrolled in this cross-sectional investigation study. We assessed anthropometric and body composition parameters. Serum IL-18 levels, physical activity by uniaxial accelerometers, peak oxygen uptake and metabolic risk parameters were also evaluated. Results Serum IL-18 levels were 179.4±84.7 pg/mL. Physical activity evaluated by Σ[metabolic equivalents × h per week (METs⋅h/w)]was significantly and negatively correlated with serum IL-18 levels (r = -0.252, p = 0.0235). These associations remained even after adjusting for age, peak oxygen uptake and other confounding factors. Conclusion Serum IL-18 levels were closely associated with physical activity independent of peak oxygen uptake in Japanese men.